Improved automated technique for the estimation of iron in ferrioxamine - Singh, A. K. (1967)
A modified automated technique for the estimation of iron in the ferrioxamine complex is described. The use of sodium dithionite as the reducing agent gave greater recovery from ferrioxamine-containing solutions when compared with a standard manual method and automated method currently used. In addition errors due to urinary pigments are eliminated by dialysis.